2022
DOI: 10.1186/s13023-022-02547-8
|View full text |Cite
|
Sign up to set email alerts
|

Improved upper limb function in non-ambulant children with SMA type 2 and 3 during nusinersen treatment: a prospective 3-years SMArtCARE registry study

Abstract: Background The development and approval of disease modifying treatments have dramatically changed disease progression in patients with spinal muscular atrophy (SMA). Nusinersen was approved in Europe in 2017 for the treatment of SMA patients irrespective of age and disease severity. Most data on therapeutic efficacy are available for the infantile-onset SMA. For patients with SMA type 2 and type 3, there is still a lack of sufficient evidence and long-term experience for nusinersen treatment. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…HFMSE was the most used scale, and trunk strength and upper limb function were captured by several items (e.g., sitting items without support, rolling items, four-point kneeling items) in the total score. Patients across the three groups reporting difficulties at the baseline perceived their upper limb function to be improved, which aligns with existing findings highlighted by patients treated with nusinersen [ 34 , 35 ]. Patients assigned to the NR group and who experienced significant improvements in upper limb function could possibly have been identified as responders by the RULM, which is more sensitive to positive upper limb function changes than HFMSE.…”
Section: Discussionsupporting
confidence: 86%
“…HFMSE was the most used scale, and trunk strength and upper limb function were captured by several items (e.g., sitting items without support, rolling items, four-point kneeling items) in the total score. Patients across the three groups reporting difficulties at the baseline perceived their upper limb function to be improved, which aligns with existing findings highlighted by patients treated with nusinersen [ 34 , 35 ]. Patients assigned to the NR group and who experienced significant improvements in upper limb function could possibly have been identified as responders by the RULM, which is more sensitive to positive upper limb function changes than HFMSE.…”
Section: Discussionsupporting
confidence: 86%
“…Published natural history studies in untreated patients with types 2 and 3 SMA (ambulant and non-ambulant) have reported decline in RULM total score over 12 months (– 0.4 points in patients aged 2.7–49.7 years) [ 25 ] and 24 months (– 0.79 points in patients aged 5–56 years) [ 26 ] and HFMSE total score over 12 months (– 0.54 points in children and adults aged ≥ 2 years with a diagnosis before 19 years of age) [ 24 ], and significant decline over 24 months in MFM32 total score (– 2.08 points in patients aged 2–30 years) [ 21 ]. Although a 2-point (RULM [ 27 ]) or 3-point (HFMSE [ 27 ], MFM32 [ 28 ]) change in these functional motor scales has been highlighted as a clinically meaningful change, stabilization in motor function is an important goal identified by patients with types 2 and 3 SMA [ 29 , 30 ] and is, thus, considered a clinically meaningful outcome in this population.…”
Section: Discussionmentioning
confidence: 99%
“…A study showed that the RULM scores of SMA in children with types II and III continue to improve, especially in older and more severe phenotypes, where improvement in HFMSE scores may be limited due to scoliosis or contracture. The RULM score seems to be more inclined to monitor changes in motor function than in patients who cannot walk alone ( 19 ). There was no significant improvement in the CHOP score in our research results, which may be related to our shorter monitoring time and smaller number of cases.…”
Section: Discussionmentioning
confidence: 99%